Archaeological research, Qolqas sector of the Raqchi archaeological park, Canchis-Cusco - Quispe Cuno, Marisa G. (2021)
This article is the preliminary result of year one, of execution with reference to the approved technical file, of the thirteen excavation units of the Qolqas sector of the Archaeological Park of Raqchi of the District of San Pedro, Province of Canchis, Cusco Department. Which focus on the associate of the cultural material evidenced and the conservation and valorization of the Qolqas sector. Its objective is to analyze the function of circular enclosures called Qolqas and establish the occupational sequence of the sector, these objectives will be developed through archaeological research in the process of archaeological research.